Structural dynamics of lithium-ion cells – Part I: Method, test bench validation and investigation of lithium-ion pouch cells. (December 2019) - Berg, Philipp; Soellner, Jonas; Jossen, Andreas
Highlights: A test bench for modal analysis of lithium-ion cells is built and validated. The structural dynamics of pouch cells show high sensitivity to temperature and SOH. The structural dynamics of pouch cells show very low sensitivity to the SOC. Lithium-ion pouch cells show nonlinear stiffness and damping behavior. Interfaces and boundaries inside the cell strongly determine the dynamic behavior. Abstract: The failure mechanisms that govern the durability of lithium-ion cells under vibration loading are inadequately investigated. It is inevitable for effective durability testing to understand what might determine damage and fatigue. Experimental modal analysis is used to unveil the structural dynamics of lithium-ion pouch cells in terms of natural frequencies, damping ratios, and mode shapes. A test bench for free-free testing has been developed and validated and is presented in this work. Sensitivities from cell parameters such as state of charge, state of health and temperature and from excitation amplitude are revealed. Strong sensitivity of the structural response from excitation amplitude due to nonlinear softening and nonlinear damping was found. Significant softening for increasing temperature with a linear regime, most probably due to changes in the visco-elasticity of the separator, was also observed, while the state of charge showed minor sensitivity. In contrast, cyclic aging caused strongly increased stiffness of the cells. The results can be used for finite element model building to accompany vibration durability research with simulations, to define which parameter sensitivities might determine the level of fatigue during vibration testing and to test the impact of high dynamic stress on lithium-ion pouch cells through resonance excitation.